Effects of magnesium sulphate on the onset time of rocuronium at different doses: a randomized clinical trial - Almeida, Carlos Eduardo David de [UNESP]; Carvalho, Lidia Raquel de [UNESP]; Andrade, Carla Vasconcelos Caspar [UNESP]; Nascimento, Paulo do [UNESP]; Barros, Guilherme Antonio Moreira de [UNESP]; Modolo, Norma Sueli Pinheiro [UNESP] (Elsevier, 2021)
Background and aims: Rocuronium may provide excellent onset time, but high doses are required for effective action. Several strategies have managed to shorten rocuronium onset time, including the use of Magnesium Sulphate (MgSO4). Methods: One hundred and eighty patients were randomized into six groups according to rocuronium dose received (0.3, 0.6 or 1.2 mg.kg-1) and the administration of saline or MgSO4 (60 mg.kg-1). Correlations between tissue perfusion and rocuronium onset time was determined by variations in perfusion index. Results: Median (quartiles) rocuronium onset times were 85.5 (74.0–92.0); 76.0 (52.0–87.0) and 50.0 (41.0–59.5) seconds for 0.3, 0.6 mg.kg-1 and 1.2 mg.kg-1 doses, respectively. MgSO4 decreased rocuronium onset at doses of 0.3 mg.kg-1 (60.0 [48.0–74.3] seconds) and 0.6 mg.kg-1 (44.0 [39.0–49.0] seconds) but not at 1.2 mg.kg-1 (38.0 [33.5–56.3] seconds) (p < 0.001). Perfusion index variations in groups that received MgSO4 were greater than in controls. A negative correlation between shorten onset and increased perfusion index was observed in rocuronium doses of 0.3 mg.kg-1 (r = -0.50; p < 0.001) and 0.6 mg.kg-1 (r = -0.424; p < 0.001), but not for 1.2 mg.kg-1 dose (r = -0.25; p = 0.07). Conclusion: MgSO4 reduces rocuronium onset time at doses of 0.3 mg.kg-1 and 0.6 mg.kg-1 being that the latter has a similar effect when compared to the dose of 1.2 mg.kg-1, with or without the use of MgSO4. Trial registry at: http://www.ensaiosclinicos.gov.br/ Registry Number: RBR-96CY3K
Keywords: Magnesium sulphate; Neuromuscular blocking agents; Rocuronium